Librarians as Drivers of Academic Integrity for Student Success at University. Issue 2 (3rd April 2022) - Gunton, Lyndelle
ABSTRACT: Concerted efforts are being directed towards academic integrity in Australia's higher education sector. University students encounter many challenges as they progress through their tertiary studies. Some of those challenges are seemingly allayed by increasingly easy opportunities to engage in deliberate or inadvertent unethical scholarly behaviours, such as contract cheating, plagiarism, or collusion. Academic librarians have much expertise to offer to the development and implementation of sustainable and scalable learning and teaching strategies as part of university-wide approaches to managing academic integrity. This article offers a case study of the development and trial of an educative strategy by a library at an Australian regional university in the form of a self-paced, online learning activity for coursework students. It demonstrates the important role of libraries and librarians in contributing to the development of evidence-based, educative approaches for preventing and reducing incidents of academic misconduct. The case study shows the critical role of librarians in engaging with students and staff in awareness raising and capacity building around ethical scholarly behaviour as students work towards those graduate attributes that form the basis for professional integrity. The article also confirms the valuable contribution librarians make to learning, teaching, and research beyond traditional academic understandings of the role of librarians.